The Genetics of Autism Spectrum Disorder- A Review - Kundu, Gopen Kumar; Islam, Rumana (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Autism spectrum disorder (ASD) is one of the most common neurodevelopmental disorders representing deficits in socialization, communication impairment, repetitive patterns of behaviors and/or restricted interest. The increasing prevalence of ASD worldwide is most likely due to increasing awareness, widening of the diagnostic concepts and availability of diagnostic framework. It is a genetically influenced disorders caused by factors including genetic, epigenetic factors that affect gene expression and activity and non-genetic factors like environmental exposures. It is widely thought to represent a disorder of connectivity, in which the environment interacts with the genome. It can occur as an association with genetic syndrome, can occur sporadically or may be familial. Recognizing various phenotypic manifestations, it is understood that the underlying etiology of ASD is complex and genetic factors play an important role. The most significant advance in autism biology over the last decade has been in understanding the genetics of autism. The genetic diagnosis can benefit patients and the family by providing information, psychological support both immediate and long term and also can guide and help to prepare for the future. So, genetic diagnosis of ASD may offer opportunities for the identification of molecular targets for novel interventions, and provide new insight for families seeking genetic counseling. J Bangladesh Coll Phys Surg 2021; 39(3): 193-199